176k views
7 votes
What is the translation rule for this transformation?

options:

T(x, y) -> (x+3, y+6)

T(x, y) -> (x-3, y-6)

T(x, y) -> (x -6, y-3)

T(x, y) -> (x+6, y+3)

What is the translation rule for this transformation? options: T(x, y) -> (x+3, y-example-1
User Li Zheng
by
5.4k points

1 Answer

7 votes

9514 1404 393

Answer:

(b) T(x, y) -> (x-3, y-6)

Explanation:

Each image point is 3 left and 6 down from the corresponding pre-image point. That is -3 is added to each x-value, and -6 is added to each y-value. That transformation is represented by ...

T(x, y) ⇒ (x-3, y-6)

User Ryon Sherman
by
5.8k points